Corona Virus Control Measures: Social Distancing Or Physical Distancing? - Ursula Ette; Ime Robson Nseobot; Anietie Imo Effiong; Vinesh Dinnoo; Nayan Deep Singh Kanwal; Edidiong Ime Frank; Esther Augustine Osom; Idiongo Okon Udia (Bina Nusantara University, 2021)
The research examines one of the Word Health Origination (WHO) measures to reduce the spread of COVID-19 which is distancing but there is a serious controversy in the used of this measure that is either “social distancing” or “physical distancing”. The research utilizes secondary sources of data and most information were explained pictorially. The research discovers that social distancing connotes distancing between different groups and class in the society whereas physical distancing refers maintaining a gap between two or more person irrespective of group and class to avoid contact. The paper concluded that the right word to use is physical distancing rather than social distancing. As part of effort to reduced COVID-19 spread, it is recommended that physical distancing should be encouraged and practiced at all times rather than social distancing.